Interview with Prof. Leon Kosals. The Police Acting in Russia Today are Consistent with Social, Economic and Political Conditions in the Country - Leon Kosals (Journal of Economic Sociology, 2018)
Leon Kosals, tenured professor at National Research University Higher School of Economics (NRU HSE), was interviewed by Elena Berdysheva, Senior Research Fellow of Laboratory for Studies in Economic Sociology at NRU HSE, in January 2018. The interview focused a role of the police in economy which belongs to Prof. Kosals’s key research interests. He has been involved into police studies since the 1990s when the existing Soviet systems were broken. Militia and its relations with the society also were transformed. Under the weak state policemen, like others, had to survive.According to Porf. Kosals, police’s informal economic activities refer to main research areas for scholars from the former USSR and Eastern Europe, while others perceive them as marginal. The most popular issues which international researchers care about include the police and visual minorities, police violence, community policing, and digital technologies and communication’ effects on police culture, etc.Additionally, Prof. Kosals discusses interactions among different disciplines in the frameworks of police studies, including possible bridges between sociology and criminology. Prof. Kosals highlights fruitful partnership between social researchers, applying scientific methods to the law and crime, and policing as one of the important achievements of multidisciplinary studies.